Managerial Ability, Financial Performance and Bankruptcy Risk - Shokrollah Khajavi (Ph.D); MohammadHossein Ghadirian Arani (مجله دانش حسابداری, 2018)
With regard to managers’ important roles in success of companies, the main purpose of this study is to examine the effects of managerial ability on the bankruptcy risk of the Iranian firms listed in the Tehran Stock Exchange, (TSE), and the mediating role of financial performance in that risk. In this study, the data came from a sample of 103 non-financing companies in the TSE from 2004 to 2015. Managerial ability of the companies was measured by the Demirjian’s model (2012). Moreover, the rate of return on assets was applied as a proxy of financial performance, and Emerging Market Scoring model (Altman's Z˝ score) was used as a measure of bankruptcy risk. The results showed that managerial ability has negative impact on bankruptcy risk. And, financial performance mediates the effect of managerial ability on bankruptcy risk. In other words, managerial ability reduces the bankruptcy risk through improving financial performance. Therefore, it could be concluded that managerial ability is an important factor in the success of the companies in TSE.